Bahasa Visual , Gambar Anak, dan Ilustrasi Pada Buku Cergam Anak - Febrina Hanisha; Yusuf Affendi Djalari (Universitas Trisakti, 2018)
AbstractVisual Language, Children’s Drawing, and Illustration of Children’s Picture Book. To create illustrations that can encourage children to interact with books is by applying visual approach appropriate to the children’s imagination and development. To understand the children’s imagination can be done by observing their drawings. Children’s drawing is the result of senses what they felt. This phenomenon is called the children’s visual language. The application of children’s visual language to illustrations can be found in contemporary children’s picture book. For example, the series of picture book “Kerlip Bintang di Langit”. Through a study of children’s drawings and illustrations of “Kerlip Bintang di Langit”, this paper is intended to analyze how the visual language correlates between children’s drawings and illustrations of children’s picture book. Also, its appropriateness to the psychology development of contemporary-children based on the periodic development of children’s visual language.Keywords: visual language, children’s drawing, illustration, picture bookAbstrakBahasa Visual, Gambar Anak, dan Ilustrasi pada Buku Cergam Anak. Salah satu cara untuk menciptakan ilustrasi yang mampu mendorong anak berinteraksi terhadap buku adalah dengan menerapkan pendekatan visual yang sesuai dengan imajinasi dan perkembangan usia anak. Cara memahami imajinasi anak dapat dilakukan dengan mengamati hasil gambarnya. Apa yang digambar oleh anak merupakan hasil kerjasama indera-indera yang mereka rasakan. Fenomena ini disebut dengan bahasa visual anak. Penerapan bahasa visual anak pada ilustrasi dapat ditemui pada buku cergam anak kontemporer. Contohnya, buku cergam “Kerlip Bintang di Langit”. Melalui kajian terhadap hasil gambar anak dan ilustrasi pada buku cergam “Kerlip Bintang di Langit”, penulisan ini dimaksudkan untuk menganalisis bagaimana korelasi bahasa visual antara gambar anak dan ilustrasi buku cergam anak. Serta, kesesuaiannya terhadap perkembangan psikologi anak-anak kontemporer berdasarkan periodesasi perkembangan bahasa visual ana